Book review: Changes in the Structure of Agriculture in Greater Poland in 1919–1939 - Machałek, Małgorzata (Studia Historiae Oeconomicae, 2025)
The book entitled Przemiany struktury rolnictwa wielkopolskiego w latach 1919–1939 [Changes in the structure of agriculture in Greater Poland between 1919 and 1939] was written by Wojciech Mielewczyk, an employee of the National Museum of Agriculture and Agricultural and Food Industry in Szreniawa, and published by Exemplum in Poznań in 2025. This comprehensive, 317-page monograph is devoted to the structure of agriculture in Greater Poland during the interwar period. The study provides an understanding of the agricultural specificity of this region and is a vital source of information for anyone interested in both regional history and the economic history of Poland.